On the Role of Fast Neutrals in the Process of Blob Formation in Low Temperature Plasmas - Sahoo, Gourishankar; Paikaray, Rita; Samantaray, Subrata; Das, Partha Sarathi; Ghosh, Joydeep; mulya Kumar, Amulya Kumar (Kathmandu University Journal of Science Engineering and Technology, 2014)
The variation of electron temperature of argon plasma with base pressure is reported using emission spectroscopy signature. It is observed that the electron temperature of plasma is < 1 eV. It is reported that at higher base pressure ~ 1 mb or above a number of prominent argon lines are observed unlike that at lower base pressure. This indicates formation of more fast neutrals inside bulk plasma at high base pressure value. Fast imaging results (~9100 fps) shows blob formation from main plasma column at base pressure 1 mb and above. For these experimental findings it can be proposed that the asymmetry force due to fast neutrals inside bulk plasma and slow neutrals outside main plasma column is responsible for blob formation at higher base pressure.